AJARAN AGAMA HINDU DALAM GEGURITAN KUNJARAKARNA - Ida Bagus Putu Eka Suadnyana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Geguritan is one of Bali literary works that is easier to understand than Kekawin sincemit uses language of Bali kepara. Geguritan divided into several stanzas. Geguritan is a media tonconvey the teachings, particularly the Hindu teachings, to the people so the readers can understand the teachings contained. Moreover, Geguritan Kunjarakarna contains of teachings and high philosophy of life. Geguritan contains of 2 elements, namely Shiva and the Buddhist religion, which is saw the presence of Wairocana (Embodiment Buddhist Deity) in the hermitage Kunjarakarna to give Dharma teachings. On the island of Java precisely in the city of Malang, Central Java, there is also a historical relic temple called the temple Jajaghu (Jago) which shows Kunjarakarna relief. The teachings of Hinduism are contained in geguritan Kunjarakarna include: a) Teaching Asta Brata that teaches about the nature of leadership; b) the teaching of Tri Hita Karana which teaches how to maintain harmonious relationship with God, the environment and each other; c) The doctrine that teaches Tri Color for love, d) The doctrine that teaches all Karmaphala no reward good deeds or bad, e) The doctrine of the existence of Atman Beliefs, f) Sad Guna and Sad Ripu that teach good and bad attitudes that exist within human.